Laboratory detection and analysis of an atypical botulism outbreak - Huiyan QIN; Hui YANG; Jiehong ZHANG; Qingbo LI (Zhongguo gonggong weisheng)
ObjectiveTo conduct laboratory detection on a suspected botulism incident and provide experimental evidence for the prevention and rapid identification of botulism. MethodsSample processing and testing were carried out according to the national standards GB4789.12–2016, GB 15193.2–2014 "National Food Safety Standard - Laboratory Operation Standards for Food Toxicology," and the instructions for botulinum toxin diagnostic serum. Mouse bioassay and diagnostic serum were used for botulinum toxin detection and confirmatory typing tests. ResultsA total of 114 SPF-grade female KM mice were used and divided into groups for detection and confirmatory typing tests. The mice were intoxicated via intraperitoneal injection. The detection test results showed that, except for the control group, animals in all sample groups exhibited typical botulism symptoms. All animals in the marinated raw fish-trypsin group, gastric contents group, and gastric contents-trypsin group died within 1–36 h. No deaths were observed in the marinated raw fish group or the blood group. The confirmatory typing test results showed that all animals in the marinated raw fish-trypsin group injected with type A, B, C, D, E, F, and A–F mixed diagnostic sera died. However, when the marinated raw fish-trypsin solution was diluted with sterile normal saline (NS) at ratios of 1:1, 1:2, and 1:3 and then reacted with type A, B, C, D, E, F, and A–F mixed diagnostic sera, no deaths occurred in the animals. Deaths were observed in all toxin control groups, but no deaths occurred in the toxin inactivation control groups. When the gastric contents-trypsin solution was diluted with NS at a 1:1 ratio and then reacted with type A, B, C, D, E, F, and A–F mixed diagnostic sera, no animal deaths occurred. However, deaths were observed in the toxin control group, while no deaths occurred in the toxin inactivation control group. According to the instructions for the botulinum toxin diagnostic serum, the poisoning was not caused by typical type A, B, C, D, E, or F botulinum toxin. It was preliminarily determined that the marinated raw fish and gastric contents contained other atypical or non-typical botulinum toxins. ConclusionsThis food poisoning incident was caused by non-A, -B, -C, -D, -E, or -F botulinum toxin.